2017
DOI: 10.1155/2017/9503857
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Multicrystalline Silicon Solar Cells by Inserting Two-Step Growth Thermal Oxide to the Surface Passivation Layer

Abstract: In this study, the efficiency of the multicrystalline was improved by inserting a two-step growth thermal oxide layer as the surface passivation layer. Two-step thermal oxidation process can reduce carrier recombination at the surface and improve cell efficiency. The first oxidation step had a growth temperature of 780°C, a growth time of 5 min, and with N 2 /O 2 gas flow ratio 12 : 1. The second oxidation had a growth temperature of 750°C, growth time of 20 min, and under pure N 2 gas environment. Carrier lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Liu et al developed the SiO 2 layer via RTO and demonstrated a 19.49 µs carrier lifetime with a nominal 0.87% reflectance [95]. An additional model developed by Liao et al produced the coating of SiO x with the RTO thermal oxidation method in two stages [96]. The developed layer indicated enhanced efficiency of the cell, minimum surface recombination velocity, and improved carrier lifetime, which is approximately 15.45 µs.…”
Section: Thermal Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al developed the SiO 2 layer via RTO and demonstrated a 19.49 µs carrier lifetime with a nominal 0.87% reflectance [95]. An additional model developed by Liao et al produced the coating of SiO x with the RTO thermal oxidation method in two stages [96]. The developed layer indicated enhanced efficiency of the cell, minimum surface recombination velocity, and improved carrier lifetime, which is approximately 15.45 µs.…”
Section: Thermal Oxidationmentioning
confidence: 99%
“…A basic economical and minimum temperature manufacturing technique must be established for confronting financial disputes. Plasma-enhanced chemical vapor deposition (PECVD) is an efficient method for passivation at the minimum cell temperature, and the substratum temperature varies from 250 to 350 • C [96][97][98]. The PECVD technique was applied for the development of a layer with SiO x for both n-type and p-type solar cells along with the assistance of CO 2 gas, temperature, and pressure.…”
Section: Plasma Enhanced Chemical Vapor Deposition (Pecvd)mentioning
confidence: 99%